2017
DOI: 10.1177/1548051817713689
|View full text |Cite
|
Sign up to set email alerts
|

Mastery Goal Orientation and Performance Affect the Development of Leader Efficacy During Leader Development

Abstract: Best-selling authors, consultants, and leadership researchers agree that confidence is integral to leader success (Chemers, Watson, & May, 2000). Popular leadership books such as Larina Kase's (2008) The Confident Leader and Bobb Biehl's (1989) Increasing Your Leadership Confidence highlight interest in the topic and imply that confidence can be learned. Ninety percent of TrainingIndustry.com's "Top 20 Companies for Leadership Training" mention increased confidence as an outcome of leader development. Likewise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(5 citation statements)
references
References 50 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…If Model 2 provided the best fit to the data, then there was evidence that company size provided some explanation for the relationship between time of survey and the outcomes studied. In all models we controlled for and Spanish vs. English survey completed as well as learning goal orientation as prior research has shown it may be linked to learning in this target population in (Johnson et al, 2018). To determine whether any other demographic variables should have been controlled for, we first observed the bi-variable relationship between demographic factors and company size.…”
Section: Discussionmentioning
confidence: 99%
“…If Model 2 provided the best fit to the data, then there was evidence that company size provided some explanation for the relationship between time of survey and the outcomes studied. In all models we controlled for and Spanish vs. English survey completed as well as learning goal orientation as prior research has shown it may be linked to learning in this target population in (Johnson et al, 2018). To determine whether any other demographic variables should have been controlled for, we first observed the bi-variable relationship between demographic factors and company size.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Dweck's work (1986), individuals with a growth mindset versus a fixed mindset approach leadership development differently (Heslin & Keating, 2017). Research on learning goal orientation that is inherent in the growth mindset shows that a goal of skill development as compared to a goal of performing well is more beneficial to learning from experience (DeShon & Gillespie, 2005;Johnson et al, 2018). Additionally, one's leader developmental efficacy (Reichard, Walker, Putter, Middleton, & Johnson, 2017) serves as a measure of individual differences in the degree to which one feels efficacious in developing leadership knowledge and skills, and plays an important role in determining how well leader development experiences translate into increasing skill acquisition or enhancing leader self-concept.…”
Section: Contextualizing Applicationmentioning
confidence: 99%
“…The first result is related to the fact that athletes with high goal orientation were significantly more successful than those with low goal orientation in a real competition environment. There are recent studies which focused on the influence of goal orientation on business performance in addition to sports Competition results based on participants' goal orientation levels performance (Domingues, Vieira, & Agnihotri, 2017;Blau, Petrucci, & Rivera, 2018;Johnson et al,2018;Zhang, Jex, Peng, & Wang, 2017;Shin, Kim, & Lee, 2016). Positive impact of high goal orientation levels on achievement in students has also been investigated by educators in different aspects (Nasiri, Pour-Safar, Taheri, Pashaky, & Louyeh, 2017;Poondej & Lerdpornkulrat, 2016;Akpur, 2016;Kaur, Noman, & Awang-Hashim, 2018).…”
Section: Discussionmentioning
confidence: 99%